The concept of assessing the risks of cybersecurity of the information system of the critical infrastructure object - Gorbenko, I.D.; Zamula О.A.; Osipenko, Yu.S. (Radiotekhnika, 2022)
Ensuring cyber and information security for critical infrastructure is achieved through the implementation of an appropriate set of information security management measures, which can be provided in the form of software policies, methods, procedures, organizational structures and functions. Information security requirements are determined, in particular, by systematic risk assessment of information security, which can be one of the elements of the predicted approach to identifying hazards in the provision of services to service participants in the information interaction of the information system. The paper presents conceptual provisions for assessing and managing cybersecurity risks of the critical infrastructure information system. The proposed concept involves the definition of: areas of security threats to the information system; involved information assets and calculation of their value; assessment of the probability of attacks on the information system; assessment of the probability of success of attacks on the information system and more. Risk assessment methods are proposed that take into account the probability of success of an attack and the probability of an attack occurring, which makes it possible to eliminate the shortcomings inherent in known approaches and provide more accurate identification of attack methods associated with the attacker’s behavior. The concept of cybersecurity risk assessment and the methodology for analyzing and assessing security threats that are presented in the work correspond to approaches to building risk-oriented information security management systems and can become the basis for developing an information security system in the information system of a critical infrastructure object.